2006
DOI: 10.1128/jb.188.1.255-268.2006
|View full text |Cite
|
Sign up to set email alerts
|

Divergence and Mosaicism among Virulent Soil Phages of the Burkholderia cepacia Complex

Abstract: We have determined the genomic sequences of four virulent myophages, Bcep1, Bcep43, BcepB1A, and Bcep781, whose hosts are soil isolates of the Burkholderia cepacia complex. Despite temporal and spatial separations between initial isolations, three of the phages (Bcep1, Bcep43, and Bcep781, designated the Bcep781 group) exhibit 87% to 99% sequence identity to one another and most coding region differences are due to synonymous nucleotide substitutions, a hallmark of neutral genetic drift. Phage BcepB1A has a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 61 publications
(57 reference statements)
1
50
0
1
Order By: Relevance
“…As in Xop2, the lysis cassette of the Xfp1-like prophage elements has an atypical gene arrangement, with the endolysin gene preceding the holin gene. The endolysin (XF0707 in Xfp1) is a glycoside hydrolase and is followed by XF0708, a homologue of the class I (3-TMD) holin from Burkholderia phage Bcep781 (56). The holin gene is followed by the Rz equivalent (XF0709 in Xfp1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in Xop2, the lysis cassette of the Xfp1-like prophage elements has an atypical gene arrangement, with the endolysin gene preceding the holin gene. The endolysin (XF0707 in Xfp1) is a glycoside hydrolase and is followed by XF0708, a homologue of the class I (3-TMD) holin from Burkholderia phage Bcep781 (56). The holin gene is followed by the Rz equivalent (XF0709 in Xfp1).…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA was sized by pulsed-field gel electrophoresis. Library preparation, sequencing, sequence assembly, and analyses were performed essentially as described previously (54,56,57). The genomic DNA library was prepared in the pSmart-LCKan vector (Lucigen).…”
Section: Methodsmentioning
confidence: 99%
“…Further investigation uncovered that all nine separate viromes generated numerous hits to phages infectious to Burkholderia: 50% of the 72 annotated protein-coding genes within the 47 399 bp genome of the Burkholderia phage BcepB1A (NC_005886) (Summer et al 2006) were found within the Lake Michigan virome. Most of the hits were from three of our original samples (Fig.…”
Section: Viral-associated Proteinsmentioning
confidence: 99%
“…The two other genes contained in this IS element, 33 and 34, are conserved hypothetical genes. gp34 is closely related to gp55 of Bcep781 and gp54 of Bcep43, both of which are virulent phages that infect the related bacterium Burkholderia cepacia (76).…”
Section: Vol 193 2011mentioning
confidence: 99%